Reliability of Shear Wave Ultrasound Elastography for Neck Lesions Identified in Routine Clinical Practice - Bhatia, K.; Tong, C. S. L.; Cho, C. C. M.; Yuen, E. H. Y.; Lee, J.; Ahuja, A. T. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: To evaluate the reliability of shear wave ultrasound elastography (SWE) in the neck.Materials and Methods: 176 neck lesions (40 thy roid, 56 lymph nodes, 46 salivary, 34 miscella neous) identified in a routine US clinic underwent SWE by one or two blinded radiologists. For this study, SWE required the operator to acquire three 10 second dynamic colour-coded SWE cineloops per lesion, select one static image per cineloop, and place circular regions-of-interest within the entire lesion and stiffest part to generate 3 SWE measurements per static image. For logistical rea sons, one radiologist evaluated all 176 lesions and the other evaluated 58 lesions. Both radiologists also reviewed 27 archived cineloops independ ently to assess SWE excluding practical technique. Reliability was assessed using intraclass correla tion coefficients (ICCs) concordance correlation coefficients (CCCs) and coefficients of repeatabil ity (CORs).Results: Test-retest ICCs for the radiologist evalu ating 176 lesions were 0.78–0.85 (fair-excellent agreement), CCCs were 0.85–0.88 (substantial agreement), and CORs were 14.9–36.1 kPa. For both radiologists evaluating 58 lesions, intra-rater and inter-rater ICCs were 0.65–0.78 and 0.72–0.77 respectively. For SWE excluding practical technique, inter-rater ICCs were 0.97–0.98 (ex cellent agreement). ICCs differed according to tis sue, being higher in thyroid lesions than lymph nodes (p < 0.001), and higher in benign than ma lignant lesions (p values < 0.001).Conclusion: Intra- and inter-rater reliability of SWE is fair to excellent according to ICCs. SWE re liability is influenced appreciably by acquisition technique. Nevertheless, CORs for SWE are not negligible. To determine whether these results are acceptable clinically, further research is re quired to establish SWE stiffness values of normal and pathological tissues in the neck.
Keywords: ultrasound; thyroid; head/neck; salivary glands; elastography